Politik Hukum Hak Asasi Manusia Tentang Kebebasan Beragama Pasca Orde Baru - Suparman Marzuki (Fakultas Hukum Universitas Islam Indonesia, 2019)
This research aims to uncoven and describe: first, the policy of state regulation in order to fulfil the right to religious freedom. Second, the concrete actions of state in taking legal steps against violations of religious freedom. This research utilizes a normative juridical method where data is collected from documents. The outcome of this research concludes that: first, Political Human Rights on the freedom of religion in Indonesia following the new order at the level of fulfilment in the form of legislation is relatively more advance and protective. Second, the strengthening of Political Human Rights at the regulatory level is not followed by changes in the legislation below it such as PNPS Law No.1 of 1965 and Article 156(a) of the Indonesian Criminal Code regarding blasphemy. Therefore, it can be concluded that Political Human Rights in Indonesia, particularly relating to the freedom of religion is a paradox. On one side it supports the products of laws and regulation which further strengthen the rights to the freedom of religion and beliefs, but on the other hand, realistically, the State actually fails to protect various forms of violations of the right to the freedom of religion and beliefs. This research aims to uncoven and describe: first, the policy of state regulation in order to fulfil the right to religious freedom. Second, the concrete actions of state in taking legal steps against violations of religious freedom. This research utilizes a normative juridical method where data is collected from documents. The outcome of this research concludes that: first, Political Human Rights on the freedom of religion in Indonesia following the new order at the level of fulfilment in the form of legislation is relatively more advance and protective. Second, the strengthening of Political Human Rights at the regulatory level is not followed by changes in the legislation below it such as PNPS Law No.1 of 1965 and Article 156(a) of the Indonesian Criminal Code regarding blasphemy. Therefore, it can be concluded that Political Human Rights in Indonesia, particularly relating to the freedom of religion is a paradox. On one side it supports the products of laws and regulation which further strengthen the rights to the freedom of religion and beliefs, but on the other hand, realistically, the State actually fails to protect various forms of violations of the right to the freedom of religion and beliefs.